Arrhyhthmogenic Right Ventricular Cardiomyopathy: From Clinical Presentation to Diagnostic and Therapeutic Challenges - A Case Report - Olivia Handayani; Ardian Rizal; Anna Fuji Rahimah (Heart Science Journal, 2020)
The diagnosis of arrhythmogenic right ventricular cardiomyopathy (ARVC) remains challenging. Detailed echocardiography is a sensitive tool for identifying structural and functional when ARVC is suspected. A thorough assessment of cardiac magnetic resonance imaging is required to further establish the diagnosis. This case illustration aimed to broaden the awareness of right ventricular cardiomyopathy among physicians, establishing the appropriate diagnostic approaches, and sensible use of implantable cardioverter-defibrillators may help to prevent unnecessary deaths.